Sustainability in the supply chain: a global logistics company case study - Gobbo, Valeria (2020)
Climate changes are an increasing cause of public and governmental concern. Therefore, environmental sustainability is a priority for a company’s potential customers and employees. Companies in the logistics sector are especially pressured to reduce their carbon footprint due to their high fossil fuel consumption. The German company Deutsche Post DHL has significantly reduced CO2emissions, while remaining profitable. This paper studies the drivers of the company’s approach to sustainability and whether this strategy is consistent with the business profitability. Using the framework of case study, I conclude that DPDHL has reduced its carbon footprint while adding value to the business.